The Place and Role of Insurance in the National Economy - Tugizova Malika Sokhib kizi (Peerian Journals Publishing, 2023)
Insurance social relations in the historical category is one. It is the society of construction of the early period from arising, gradually has become an integral companion of the social production. Primary insurance of the phrase meaning "fear" the word is associated with. Production property owners into relationship with each other unless they are entered in the property to maintain, natural disasters, fire, theft and the other set of economic life , not keeping risk as a result.
Keywords: social relations; risk character; easy distribution